Antipsychotic treatment of very late-onset schizophrenia-like psychosis (ATLAS): a randomised, controlled, double-blind trial. (July 2018) - Howard, Robert; Cort, Elizabeth; Bradley, Rosie; Harper, Emma; Kelly, Linda; Bentham, Peter; Ritchie, Craig; Reeves, Suzanne; Fawzi, Waleed; Livingston, Gill; Sommerlad, Andrew; Oomman, Sabu; et al.
Summary: Background: Very late (aged ≥60 years) onset schizophrenia-like psychosis occurs frequently but no placebo-controlled, randomised trials have assessed the efficacy and risks of antipsychotic treatment. We investigated whether low-dose amisulpride (100 mg daily) is superior to placebo in reducing psychosis symptoms over 12 weeks and whether any benefit is maintained by continuing treatment after 12 weeks. Methods: The ATLAS double-blind controlled trial enrolled participants from 25 old age psychiatry services in the UK. Eligible participants (ie, those with a diagnosis of very late-onset schizophrenia-like psychosis and a Brief Psychiatric Rating Scale [BPRS] score of ≥30, without cognitive impairment) were randomly assigned (1:1:1) to one of three groups in a two-stage trial: amisulpride in stage 1 and 2 (group A), amisulpride then placebo (group B), or placebo then amisulpride (group C). Treatment (100 mg oral amisulpride daily vs placebo) was given for 12 weeks in stage 1 and, initially, 24 weeks then reduced to 12 weeks in stage 2. Participants, investigators, and outcome assessors were masked to treatment allocation. Primary outcomes were psychosis symptoms assessed by the BPRS at 4, 12, and 24, or 36 weeks, and trial treatment discontinuation for non-efficacy. The primary, secondary, and safety endpoints were all analysed in participants given at least one dose of study treatment in modified intention-to-treat analyses. This study is registered with EudraCT, number 2010-022184-35, and ISRCTN, number ISRCTN45593573. Findings: Between Sept 27, 2012, and June 28, 2016, we recruited 101 participants. 92 (91%) of 101 participants took trial medication, of whom 59 (64%) completed stage 1 and 34 (58%) of these 59 participants completed stage 2 treatment. Despite suboptimal compliance, improvements in BPRS scores at 12 weeks were 7·7 points (95% CI 3·8–11·5, p=0·0002) greater with amisulpride (mean 11·9 points [SE 1·3]) than with placebo (4·2 points [1·0]). In stage 2, BPRS scores improved by a mean of 1·1 points (1·6) from 12 weeks to the final assessment in those who continued amisulpride but deteriorated by 5·2 points (2·0) in those who switched from amisulpride to placebo (difference 6·3 points [95% CI 0·9–11·7], p=0·024). Fewer participants who were allocated amisulpride than placebo stopped treatment because of non-efficacy in stage 1 (p=0·010) and stage 2 (p=0·031). Serious adverse events were reported more frequently in the amisulpride group than in the placebo group in stage 1 (p=0·057) and stage 2 (p=0·19). The most common serious adverse events were infection (five patients in the amisulpride group, three in the placebo group) and extrapyramidal side-effects (three patients in the amisulpride group, none in the placebo group). Five patients died during the study, one from a gastric ulcer bleed before treatment started (group B), two while taking stage 2 treatment (one in group A and one in group C), and two who stopped trial treatment in stage 1 and died many weeks later (one in group B and one in group C). No deaths were related to treatment. Interpretation: Low-dose amisulpride is effective and well tolerated as a treatment for very late-onset schizophrenia-like psychosis, with benefits maintained by prolonging treatment. Funding: UK National Institute for Health Research.